Alleviation of Cartilage Destruction by Sinapic Acid in Experimental Osteoarthritis. (26th February 2019) - Cai, Dawei; Huff, Thomas W.; Liu, Jun; Yuan, Tangbo; Wei, Zijian; Qin, Jian
Abstract : Sinapic acid (SA) modulates the nuclear factor-erythroid 2-related factor 2 (Nrf2) signaling pathway in chondrocytes. In order to test the hypothesis that SA is protective against the development of osteoarthritis (OA), primary mouse chondrocytes were treated in vitro with SA and the promoter transactivation activity of heme oxygenase 1 (HO-1), nuclear translocation of Nrf2, and protein expression of HO-1 were assayed. To test the hypothesis in vivo, a destabilization of the medial meniscus (DMM) model was used to induce OA in the knees of mice and SA was delivered orally to the experimental group. The chondrocytes were harvested for further analysis. The expression of HO-1 was similarly upregulated in cartilage from both the experimental mice and human chondrocytes from osteoarthritic knees. SA was found to enhance the promoter transactivation activity of heme oxygenase 1 (HO-1) and increase the expression of Nrf2 and HO-1 in primary chondrocytes. Histopathologic scores showed that the damage induced by the DMM model was significantly lower in the SA treatment group. The addition of a HO-1 inhibitor with SA did not show additional benefit over SA alone in terms of cartilage degradation or histopathologic scores. The expression of TNF- α, IL-1 β, IL-6, MMP-1, MMP-3, MMP-13, ADAMTS4, and ADAMTS5 was significantly reduced both in vitro and in vivo by the presence of SA. Protein expressions of HO-1 and Nrf2 were substantially increased in knee cartilage of mice that received oral SA. Our results suggest that SA should be further explored as a preventative treatment for OA.